1989
DOI: 10.1007/bf03220795
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundaries and Jc in High-Tc Oxide Superconductors

Abstract: In metallic superconductors, grain boundaries are effective pinners of magnetic flux and, as such, are partially responsible for high critical current densities achievable in those materials. However, in the highcritical-temperature oxide superconductors, grain boundaries have been identified as the source of problems leading to the low critical current densities exhibited by bulksintered material. The very short superconducting coherence lengths of the oxides make their electrical and magnetic properties exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The phenomenon of reduced Jc due to poor electrical connectivity across GBs is called weak-link behavior. Possible sources for producing the weak-link effect include intrinsic anisotropy of the superconducting properties, the presence of structural disorder at grain boundaries [13,14], microcracking due to thermal and transformational stresses [19,20], and the presence of nonstoichiometric material at GBs [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of reduced Jc due to poor electrical connectivity across GBs is called weak-link behavior. Possible sources for producing the weak-link effect include intrinsic anisotropy of the superconducting properties, the presence of structural disorder at grain boundaries [13,14], microcracking due to thermal and transformational stresses [19,20], and the presence of nonstoichiometric material at GBs [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Auger spectroscopy [21,23,24] and analytical electron microscopy [19,22,[25][26][27] studies have shown the presence of grain boundary films and variations in copper and oxygen stoichiometry. More recently, TEM and parallel-detection electron energy-loss spectroscopy (EELS) [28] have been applied to characterize the correlation between the crystallographic misorientations of the Y123 grain boundaries and oxygen deficiency at the boundaries.…”
Section: Introductionmentioning
confidence: 99%